Detection of early osteoarthritis by in vivo optical imaging of an antibody specific to type ii collagen damaged by reactive oxidants - Lim, N; Vincent, A; Nissim, A (Elsevier, 2016)
To determine if the 1-11E single chain fragment variable (scFv) or monoclonal antibody (mAb) which recognises type II collagen modified by reactive oxidant species, could serve as an imaging biomarker for early disease in experimental osteoarthritis (OA).